Right and left prefrontal transcranial magnetic stimulation at 1 Hz does not affect mood in healthy volunteers - Jenkins, J; Shajahan, P; Lappin, J; Ebmeier, K (BioMed Central, 2002)
Background: Prefrontal repetitive transcranial magnetic stimulation (rTMS) has been used to induce side-specific mood changes in volunteers and patients. To clarify inconsistencies between reports that used different stimulation frequencies, we conducted a controlled study with a low (1 Hz) frequency, comparing left with right-sided stimulation. Methods: Nineteen healthy volunteers received randomised left or right prefrontal rTMS at a frequency of 1 Hz and 100% of motor threshold in two sessions two weeks apart. Results: There were significant improvements with TMS for performance in the digit symbol substitution and verbal fluency tests, but no change of mood on a number of measures. There was also a reduction of pulse rate after TMS. The only side-specific TMS-effect was on mean arterial pressure, which decreased pressure after left, but not after right prefrontal TMS. Conclusions: Apart from the unexpected and so far unreplicated effect on mean arterial pressure, there were no side-specific effects on mood in volunteers. It is unlikely that a simple laterality model of mood together with the assumed activating effect of higher and 'quenching' effect of lower stimulation frequency can account for the effects of TMS on mood.